Analysis of Student Development Programs in Strengthening The Religious Diversity of Muslim Youth in The Digital Age - Hafilda Anisa; Anis Fahrurozi; A’Idatul Islahiah; Unung Lisnawati; Egi Yusuf Maulana; Teti Ratnasih; Andewi Suhartini (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
This study analyzes student development programs aimed at strengthening the religious identity of Muslim youth in the digital age, conducted at a modern Islamic boarding school in Subang Regency. It focuses on program effectiveness, the influence of digital technology, the role of educators, and student responses. A phenomenological qualitative approach was applied to explore participants’ lived experiences. Participants included 12 students, 3 boarding school teachers, 1 character-building teacher, 4 Islamic education teachers, and 2 murobbi, selected purposively based on their involvement in the guidance program. Data were collected through structured and open-ended online interviews via Google Form, supported by documentation and behavioral observation. Analysis followed Miles and Huberman’s interactive model: data reduction, display, and verification through triangulation and member checking. Findings indicate that the program effectively strengthens religiosity through educator collaboration in activities such as congregational prayer, Qur’an recitation, spiritual studies, and digital ethics, enhancing student discipline and independence. Religious identity was reinforced through modeling, evaluation, and discussion, though digital distractions required close supervision. The roles of character-building teachers, Islamic education staff, and dormitory supervisors complemented one another, including innovations using digital media. Students’ responses were generally positive, influenced by internal and external motivations. Overall, the program fosters adaptive religiosity in the digital era while requiring improved monitoring and flexibility for sustainable outcomes.